Csempelevél . Tile Mail - Somogyvári, Gergő; Feszt, Judit (Hungary, 2008)
Verzio FF Set in Lisbon, this film is Nober Sanders’ Super 8 film-letter to his distant family. This personal visual testament explores the boundaries of immigration and integration. Nober learnt the art of painting Portuguese tiles, azulejos, by which he still earns his living today. A juxtaposition of tile and man, the film uncovers the impact various cultures had on both. While the Portuguese azulejo was transformed under Spanish, Chinese, Dutch, Arabic, Indian, Brazilian and African cultural influences, Nober ponders his own metamorphosis while painting tiles one by one.